Frontal plane pelvic kinematics during high velocity running: Association with hamstring injury history - Nurse, C. A.; Lewis, C. L.; Shefelbine, S. J. (Physical Therapy in Sport, 2023)
Introduction Hamstring injuries are the most prevalent non-contact soft tissue injury in sports, with a larger portion of injuries being recurrent. The sagittal plane running kinematics correlated to hamstring injury history has been well documented. However, analysis of frontal plane kinematics allows for observation of stability and symmetry. This study aimed to examine the frontal plane running kinematics of elite collegiate level sprinters, with and without previous hamstring injury, compared to healthy counterparts.